Business Information Systems : 19th International Conference, BIS 2016, Leipzig, Germany, July, 6-8, 2016, Proceedings /: 19th International Conference, BIS 2016, Leipzig, Germany, July, 6-8, 2016, Proceedings. (2016) - Unknown
No abstract available